(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
MSME Dodol Salak Kuningan is a potential MSME, but has several problems, especially the use of technological tools that are still simple, this causes business processes to become less effective and efficient so that product competitiveness is low. The solution provided by the UGJ PKM TEAM is to implement the Implementation of Effective Manufacturing Management on MSME Processed Salak Products in Cimara Village, Pasawahan District, Kuningan Regency. The PKM activity method uses a Participatory Learning and Action (PLA) approach. The stages of this activity are carried out through several stages, namely: 1) observation on MSMEs, 2) socialization of the implementation of effective manufacturing management 3) Training and assistance in technology adaptation, 4) Monitoring, evaluation and follow-up, 5) Compilation of reports and publications. The results of PKM activities: 1) Application of salak fruit grinding machine technology, 2) Application of automatic dodol stirring machine technology, 3) Improvement of product packaging. Based on the evaluation of PKM activities, it can be concluded that PKM activities have an impact on: 1) The production process is faster and more efficient, 2) Better product quality, 3) Increased product competitiveness.